Modulation of the Antitumor Activity of Metronomic Cyclophosphamide by the Angiogenesis Inhibitor Axitinib - Ma, Jie (2008)
The promising but still limited efficacy of angiogenesis inhibitors as monotherapies for cancer treatment indicates a need to integrate these agents into existing therapeutic regimens. Presently, we investigate the anti-tumor activity of the small molecule angiogenesis inhibitor axitinib (AG-013736) and its potential for combination with metronomic cyclophosphamide (CPA). Axitinib significantly inhibited angiogenesis in rat 9L tumors grown s.c. in scid mice, but only moderately delayed tumor growth. Combination of axitinib with metronomic CPA fully blocked 9L tumor growth upon initiation of drug treatment. In contrast, metronomic CPA alone required multiple treatment cycles to halt tumor growth. However, in contrast to the substantial tumor regression that is ultimately induced by metronomic CPA, the axitinib/CPA combination was tumor growth static. Axitinib did not inhibit hepatic activation of CPA or export of its activated metabolite, 4-OH-CPA, to extrahepatic tissues; rather, axitinib selectively decreased 9L tumor uptake of 4-OH-CPA by 30–40%. The reduced tumor penetration of 4-OH-CPA was associated with a decrease in CPA-induced tumor cell apoptosis and a block in the induction of the endogenous angiogenesis inhibitor TSP-1 in tumor-associated host cells, which may contribute to the absence of tumor regression with the axitinib/CPA combination. Finally, axitinib transiently increased 9L tumor cell apoptosis, indicating that its effects are not limited to the endothelial cell population. These findings highlight the multiple effects that may characterize anti-angiogenic agent–metronomic chemotherapy combinations, and suggest that careful optimization of drug scheduling and dosages will be required to maximize anti-tumor responses.